Tobacco use, exposure to secondhand smoke, and cessation counseling among medical students: cross-country data from the Global Health Professions Student Survey (GHPSS), 2005-2008 - Lea Veronica; Lee Juliette; Sinha Dhirendra N; Warren Charles W; Jones Nathan R (BMC, 2011)
Abstract Background GHPSS is a school-based survey that collects self-administered data from students in regular classroom settings. GHPSS produces representative data at the national or city level in each country. This study aims to investigate the prevalence of tobacco use, exposure to secondhand smoke, and cessation counseling among medical students using the GHPSS data. Methods The Global Health Professions Student Survey (GHPSS) was conducted among 3rd year medical students in 47 countries and the Gaza Strip/West Bank from 2005-2008 to determine the prevalence of tobacco use and amount of formal training in cessation counseling. Results In 26 of the 48 sites, over 20% of the students currently smoked cigarettes, with males having higher rates than females in 37 sites. Over 70% of students reported having been exposed to secondhand smoke in public places in 29 of 48 sites. The majority of students recognized that they are role models in society (over 80% in 42 of 48 sites), believed they should receive training on counseling patients to quit using tobacco (over 80% in 41 of 48 sites), but few reported receiving formal training (less than 40% in 46 of 48 sites). Conclusion Tobacco control efforts must discourage tobacco use among health professionals, promote smoke free workplaces, and implement programs that train medical students in effective cessation-counseling techniques.